2020
DOI: 10.1038/s41431-020-00742-4
|View full text |Cite
|
Sign up to set email alerts
|

X Chromosome inactivation: a modifier of factor VIII and IX plasma levels and bleeding phenotype in Haemophilia carriers

Abstract: Haemophilia A and B are X-linked hemorrhagic disorders caused by gene variants in the F8 and F9 genes. Due to recessive inheritance, males are affected, while female carriers are usually asymptomatic with a wide range of factor VIII (FVIII) or IX (FIX) levels. Bleeding tendency in female carriers is extremely variable and may be associated with low clotting factor levels. This could be explained by F8 or F9 genetic variations, numerical or structural X chromosomal anomalies, or epigenetic variations such as ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Variability in factor levels among HCs is poorly understood and more research is needed to find out whether there is a relationship between the type of gene mutation and plasma FVIII/IX level in HCs 13 . Rarely, a woman may inherit an affected X chromosome from both parents, leading to full expression of the hemophilia variant’s severity, or exhibit moderate/severe hemophilia due to an extremely skewed X chromosome inactivation pattern 14,15 . In addition, approximately one in four HCs with normal FVIII/IX levels >0.50 IU/ml have an increased bleeding tendency 16–18 .…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Variability in factor levels among HCs is poorly understood and more research is needed to find out whether there is a relationship between the type of gene mutation and plasma FVIII/IX level in HCs 13 . Rarely, a woman may inherit an affected X chromosome from both parents, leading to full expression of the hemophilia variant’s severity, or exhibit moderate/severe hemophilia due to an extremely skewed X chromosome inactivation pattern 14,15 . In addition, approximately one in four HCs with normal FVIII/IX levels >0.50 IU/ml have an increased bleeding tendency 16–18 .…”
Section: Background and Rationalementioning
confidence: 99%
“… 13 Rarely, a woman may inherit an affected X chromosome from both parents, leading to full expression of the hemophilia variant’s severity, or exhibit moderate/severe hemophilia due to an extremely skewed X chromosome inactivation pattern. 14 , 15 In addition, approximately one in four HCs with normal FVIII/IX levels >0.50 IU/ml have an increased bleeding tendency. 16 , 17 , 18 In hemophilia A carriers this may in part be due to an impaired FVIII response to hemostatic stress.…”
Section: Background and Rationalementioning
confidence: 99%
“…Garagiola et al [29] have recently reported that low FVIII activity in HA carriers is associated with skewed XCI. Of note, analysis of XCI patterns in our cohort of HA carriers at the Israeli National Hemophilia Center revealed no evidence of significant correlation between XCI patterns and FVIII levels (data not shown), which is in agreement with the lack of correlation between XCI patterns and FVIII levels in HA carriers reported by Orstavik [30].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical symptoms in carriers of X-linked diseases depend on the levels of the main protein in the affected tissues. Several mechanisms have been hypothesized such as gene mutation on both alleles [ 100 ], loss of one X chromosome as in Turner’s Syndrome [ 101 , 102 ], uniparental disomy [ 103 ] or skewed X chromosome inactivation (XCI), with preferential inactivation of the X chromosome carrying the normal allele [ 92 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Skewed X-chromosome Inactivationmentioning
confidence: 99%
“…Previous studies have shown the correlation between skewed XCI and phenotype in carriers of X-linked diseases, such as Duchenne and Becker muscular dystrophies [ 104 , 106 , 107 , 108 ], EDMD1 or myotubular myopathy [ 124 ], haemophilia B [ 125 , 126 ], dyskeratosis congenita [ 127 ], retinitis pigmentosa [ 128 ], Lesch-Nyhan disease, haemophilia A [ 110 , 125 ], Rett-syndrome and others. In fact, skewed XCI, resulted in a higher percentage of mutant cells than normal cells and could lead to clinical symptoms in X-linked disease ( Figure 2 ).…”
Section: Skewed X-chromosome Inactivationmentioning
confidence: 99%